(untitled) (Bangladesh Journal of Botany, 2024)
A field experiment was conducted to investigate the effect of foliar application of NAA at varying N-levels on growth and yield responses of BARI Sweet Corn-1 (Zea mays L.). The trial consisted of ten treatments viz. control = without NAA and N fertilizer; RDN (recommended dose of N fertilizer); 25 ppm NAA + RDN; 50 ppm NAA + RDN; 25 ppm NAA + 50% higher RDN; 50 ppm NAA + 50% higher RDN; 25 ppm NAA + 100% higher RDN; 50 ppm NAA + 100% higher RDN; 25 ppm NAA+ 150% higher RDN and 50 ppm NAA + 150% higher RDN. Results showed that application NAA in combination with various nitrogen (N) levels produced better growth than control but with few exceptions. Growth parameters viz. total dry mater (TDM), leaf area (LA), relative growth rate (RGR) and net assimilation rate (NAR) were recorded maximum from 25 ppm NAA in combination with RDN treatment. Findings revealed that 25 ppm NAA in combination with RDN treatment had also produced higher number of leaves per plant, specific leaf area (SLA), biomass duration (BMD) and absolute growth rate (AGR) than RDN treatment although statistically at par to each other. The maximum number of leaves per plant, shoot-root ratio and SLA although recorded maximum from 25 ppm NAA in combination with 100% higher RDN treatment but statistically similar to rest of the combined treatments. Yield attributes and yield of BARI Sweet Corn-1 showed positive response to NAA at varying N-levels with significant variations in majority of cases. The maximum number of cobs and productive cobs per plant, dry weight of cobs, length of cob, number of seed per row and cob, dry weight of tassel, yield per plant and harvest index were also obtained from 25 ppm NAA in combination with RDN treatment. However, maximum number of cobs and productive cobs per plant were also noted from 25 ppm NAA in combination with 100% higher RDN treatment. Significantly maximum yield per plant (114.41g) obtained from 25 ppm NAA in combination with RDN treatment which was 12.02% higher over RDN treatment. Out of ten treatments, foliar application of 25 ppm NAA in combination with RDN treatment produced better stimulation in growth and yield of BARI Sweet Corn-1. Bangladesh J. Bot. 53(2): 337-344, 2024 (June)